INTEGRASI SISTEM PEMBAYARAN NON-TUNAI DALAM KERANGKA EKONOMI SYARIAH: ANALISIS KOMPATIBILITAS DAN IMPLIKASI - Zuchroh, Imama (CV. Lafadz Jaya, 2024)
This research examines the integration of cashless payment systems within the framework of Islamic economics, focusing on compatibility analysis and implications. Through a qualitative descriptive approach based on library research, this study investigates the alignment of digital payment technologies with Islamic financial principles. In-depth analysis of contemporary literature, Islamic scholarly opinions, and industry reports is conducted to identify potential synergies and challenges in the adoption of cashless payment systems by Islamic financial institutions. The findings reveal significant opportunities for innovation in Islamic fintech, while also highlighting the need for a comprehensive regulatory framework to ensure compliance with maqasid shariah. This research contributes to a deeper understanding of the dynamics between financial technological advancements and Islamic economic principles, providing a foundation for the development of innovative Islamic financial policies and products in the digital era.